A gazdasági válság lehetséges környezeti ajándékhatásai a visegrádi négyek országaiban - Karcagi-Kováts, Andrea; Kovács, István; Dombi, Mihály; Kuti, István (Közép-Európai Közlemények, 2016)
There are numerous studies of the negative short-run effects of the financial and economic crisis of 2008 on the society and economy. In this paper, we analyse the possible environmental side-effects in the countries of Visegrad Four as a gift of the crisis and the permanence of these “gift-effects” in the long run. Since population does not change significantly, in our region the anthropogenic pressure on the ecological systems is fed by two processes, namely by production and consumption. We use two indicators of the input side of Material Flow Analysis (MFA), which is a set of environmental indicators that describes social metabolism. By applying Direct Material Input (DMI) and Total Material Requirement (TMR) we study the chances of the process of dematerialisation between 1996 and 2011, which process is urged by many.